2020
DOI: 10.1038/s41467-020-19194-x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed reductive coupling of homoenolates and their higher homologues with unactivated alkyl bromides

Abstract: The catalytic generation of homoenolates and their higher homologues has been a long-standing challenge. Like the generation of transition metal enolates, which have been used to great affect in synthesis and medicinal chemistries, homoenolates and their higher homologues have much potential, albeit largely unrealized. Herein, a nickel-catalyzed generation of homoenolates, and their higher homologues, via decarbonylation of readily available cyclic anhydrides has been developed. The utility of nickel-bound hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…To further demonstrate that the alkyl bromide might follow the radical pathway, a radical clock experiment was carried out. 13,12 d We used the cyclopropylmethyl bromide 2q as a coupling reagent under the standard conditions, and the cross-coupling product 3qa was not detected ( Scheme 3b ). The reaction resulted in a mixture of products; it was found that the reaction generates the ring-opened products 3qb, 3qc and 3qd in a total 51% yield, and the ratio of 3qb : 3qd : 3qe is about 2 : 0.4 : 2.4.…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate that the alkyl bromide might follow the radical pathway, a radical clock experiment was carried out. 13,12 d We used the cyclopropylmethyl bromide 2q as a coupling reagent under the standard conditions, and the cross-coupling product 3qa was not detected ( Scheme 3b ). The reaction resulted in a mixture of products; it was found that the reaction generates the ring-opened products 3qb, 3qc and 3qd in a total 51% yield, and the ratio of 3qb : 3qd : 3qe is about 2 : 0.4 : 2.4.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, to avoid the handing of less-stable organometallic reagents and improve the efficiency of coupling reactions, the direct cross-couplings of two different electrophiles has received tremendous attention in the synthetic community . These “one-pot” reactions involving two different electrophilic coupling partners could be achieved by relying on a catalytic amount of the transition metal (e.g., Pd, Ni, Co, and Fe) and stoichiometric amounts of the reducing metal (e.g., Zn, Mn, and Mg) . As a continuation of our group’s endeavor to develop transition-metal-catalyzed direct cross-couplings of two different electrophiles, herein we report a direct cross-coupling of diaryl sulfoxide with aryl bromide.…”
mentioning
confidence: 99%
“…Recent reports by Ma and co-workers on the palladium-catalyzed coupling between cyclopropanols and propargyl carbonates or 2,3-allenic carbonates suggest the feasibility of such transformations, 5 while their studies underlined the difficulty of suppressing β-hydride elimination of palladium homoenolate to give enone as an undesirable byproduct. 6 We report herein a nickel-catalyzed ring-opening coupling between cyclopropanols and various allylic carbonates with linear selectivity (Scheme 1c), which involves catalytically generated nickel homoenolate as the key intermediate 7,8 allylation. The present reaction features neutral and noncryogenic conditions without using stoichiometric metal reagents and allows the use of linear, branched, and cyclic allylic carbonates, thus offering an approach to various δ,εunsaturated ketones that is complementary to others such as the conjugate addition of allyl nucleophiles 9 or enolate alkylation with homoallyl electrophiles.…”
mentioning
confidence: 99%